2020
DOI: 10.1007/s00125-020-05102-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma β-amyloid 40 and 42 concentration with type 2 diabetes among Chinese adults

Abstract: Aims/hypothesis There is evidence for a bidirectional association between type 2 diabetes and Alzheimer's disease. Plasma βamyloid (Aβ) is a potential biomarker for Alzheimer's disease. We aimed to investigate the association of plasma Aβ40 and Aβ42 with risk of type 2 diabetes. Methods We performed a case-control study and a nested case-control study within a prospective cohort study. In the casecontrol study, we included 1063 newly diagnosed individuals with type 2 diabetes and 1063 control participants matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…There was a negative correlation between Mir-155 levels and diabetes patients with different levels of obesity. Peng et al (23) statistically compared the changes of Aβ1-42 levels in diabetic patients and the control group, and the results showed that the risk of diabetes increased with the increase of Aβ1-42 levels, and the two were positively correlated. The results of this study showed that PPAR γ and Mir-155 levels were negatively correlated with pre-diabetes, mild and moderate diabetes, while Aβ1-42 was positively correlated with pre-diabetes, mild and moderate diabetes.…”
Section: Predictive Efficacy Of Pparγ Aβ1-42 and Mir-155 Levels On The Occurrence And Development Of Diabetes Mellitusmentioning
confidence: 99%
“…There was a negative correlation between Mir-155 levels and diabetes patients with different levels of obesity. Peng et al (23) statistically compared the changes of Aβ1-42 levels in diabetic patients and the control group, and the results showed that the risk of diabetes increased with the increase of Aβ1-42 levels, and the two were positively correlated. The results of this study showed that PPAR γ and Mir-155 levels were negatively correlated with pre-diabetes, mild and moderate diabetes, while Aβ1-42 was positively correlated with pre-diabetes, mild and moderate diabetes.…”
Section: Predictive Efficacy Of Pparγ Aβ1-42 and Mir-155 Levels On The Occurrence And Development Of Diabetes Mellitusmentioning
confidence: 99%
“…The EZSZ was initiated to investigate the impacts of nutrition, lifestyle, and genetic factors with chronic diseases in Ezhou and Shenzhen city (in China). Ezhou cohort had been described in our previous report [31]. Briefly, between 2013 and 2015 in Ezhou and between 2017 and 2020 in Shenzhen, 9328 adult residents were enrolled for a baseline investigation.…”
Section: Study Populationmentioning
confidence: 99%
“…Furthermore, it has Natural and Life Sciences Communications: https://cmuj.cmu.ac.th been demonstrated that plasma Aβ1-42 levels were negatively correlated with the cognitive performance of individuals with mild cognitive impairment (MCI) and individuals with AD (Nakamura et al, 2018). However, studies of Aβ1-42 levels in people with diabetes or in an animal model of diabetes were inconclusive (Peters et al, 2017;Meakin et al, 2020;Peng et al, 2020). In our study, we found that diabetic mice exhibited a decrease in plasma Aβ1-42 levels when compared to control mice and the treatment with metformin normalized the levels of plasma Aβ1-42 in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%